DAMPAK PROGRAM PAJALA TERHADAP PRODUKTIVITAS PADI SAWAH DI DESA JONO OGE KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Muh Dwi Saputra; Made Antara; Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This research aimed to identify the impact of Pajala program on the productivity of wetland rice in JonoOgevillage, Sigi Biromaru Sub District, Sigi Regency. This research was conducted in September to November 2017. The respondents of 32 farmers were determined using a simple random sampling method.  The tool used to analyze data in this research wast dependent test. The results of t dependent test indicated that the rice productivity was higher after the Pajala program was implemented with the correlation of 0.763 or 76.3%. This suggests that the Pajala as a government program has a positive impact on the farmer by improving their welfare through increasing wetland rice productivity.